Macroalgae host pathogenic Vibrio spp. in a temperate estuary - Geisser, Alexandra H.; Scro, Abigail K.; Smolowitz, Roxanna; Fulweiler, Robinson W. (Frontiers in Marine Science, 2025)
Anthropogenic climate change is altering coastal systems globally, affecting macroalgae abundance and composition. These macroalgae host diverse microbiomes, including pathogenic bacteria. Of particular concern are Vibrio species, such as Vibrio parahaemolyticus and Vibrio vulnificus, which are linked to human disease and impact public health, the economy, and recreation in coastal areas. This study examined the presence and abundance of pathogenic Vibrio spp. across seven genera of macroalgae in a temperate estuary (Narragansett Bay, RI, USA). Using colony-forming unit (CFU) counts and multiplex qPCR, we quantified V. parahaemolyticus and V. vulnificus abundance to assess if pathogenic Vibrio abundance varied by macroalgae genus and morphology. We also examined potential environmental factors influencing pathogenic Vibrio prevalence. We demonstrate that both V. vulnificus and V. parahaemolyticus were present on all macroalgae genera, with V. vulnificus showing higher average abundance. Environmental factors like temperature, salinity, and nutrient concentrations did not strongly correlate with V. vulnificus or V. parahaemolyticus abundance, suggesting that macroalgae might offer a protective microhabitat for these pathogens. Macroalgae with opportunistic life strategies had the highest abundance of V. vulnificus and V. parahaemolyticus, highlighting their potential role as reservoirs for pathogenic Vibrio spp. Future research should explore broader environmental contexts and macroalgae–Vibrio spp. interactions to better understand and forecast pathogen dynamics.